Suoi Cun Au ore occurrence as an example of potential Carlin-type sulphide-gold mineralization in northeast Vietnam - Nevolko, Petr A.; Tran, Tuan Anh; Svetlitskaya, Tatiana V.; Tran, Trong Hoa; Ngo, Thi Phuong; Ngo, Thi Huong (Геосферные исследования)
The territory of the northeast of Vietnam is the most important region of the country in terms of metallogeny, especially for precious and non-ferrous metals. A large number of Au, Pb, Zn, Sb, Hg, and Ni-Cu-PGE deposits are located in this territory, regionally confined to the southwestern margin of the South China Block. This region is located northeast of the Red River Shear Zone, which marks the boundary between two large geoblocks. The Song Hien rift basin is an important metallogenic region of northeastern Vietnam and extends for more than 200 km in the NW-SE direction, up to the state border with China. On the adjacent territory of China, the Song Hien structure passes into the Youjiang rift basin, where a large number of gold deposits attributed to the Carlin formation are also known. The Suoi Cun deposit is located to the east and southeast of the Cao Bang city and the large Cu-Ni-Pt-bearing mafic-ultramafic Suoi Cun massif. The mineralization is hosted by the rhyolites of the Triassic Song Hien formation and represents by hydrothermal low-temperature veins and crushing zones with chalcedonic quartz. Ore minerals in quartz-vein and metasomatically altered rhyolites are represented by pyrite, marcasite, and arsenopyrite. The amount of ore minerals is not constant and varies in a wide range from poor dissemination to 30 %. Ore zones have a zonal structure. The outer zones, 50–100 meters wide, are represented by altered rhyolites. The central part of the ore bodies is ore breccia, the fragments of which are represented by both massive pyrite aggregates and differently altered and mineralized rhyolites. The cement of the breccias is different and depends on the spatial position in the section of the ore body. The outer part of the inner mineralized zone is cemented by quartz and, more rarely, by carbonate. According to the results of Ar-Ar dating, the calculated age of hydrothermal sericite from the axial part of the mineralized zone was 218 ± 1 Ma. The main geological and mineral characteristics of the Suoi Cun deposit include: (1) the confinement of mineralization to zones of crushing and multiple breccia formation in the rhyolites of the Song Hien Formation; (2) wide development of chalcedonic quartz and marcasite, indicating low temperatures of mineral formation; (3) chloritization, sericitization, silicification, and sulfidization as the dominant types of metasomatic transformation; (4) mineral association represented by pyrite, marcasite, arsenopyrite, and stibnite; (5) absence of native gold in ores, positive correlation between gold and Carlin group elements (As, Sb, Hg, Tl); (6) relation of mineral formation with regional tectonic events, lack of genetic relationship with magmatism. Using the critical characteristics for Carlin type deposits, we conclude that the Suoi Cun deposit is represented by this formation.